Description of the Level of Student Creativity in Solving Open-Ended Mathematical Problems at SMA Negeri 1 Polewali, Polewali Mandar Regency - Alimuddin Alimuddin; Nasrullah Nasrullah; Muftihul Hijrah (Program of Mathematics Education Department of Mathematics Faculty of Mathematics and Natural Sciences (FMIPA) Universitas Negeri Makassar (UNM), 2025)
This study aims to determine the level of students' initial abilities, the level of student creativity, and the effect of initial abilities on student creativity in solving open-ended math problems in class X Merdeka 8 SMA Negeri 1 Polewali. The research method used is mixed-method with sequential explanatory design. The research subjects consisted of 38 students selected using purposive sampling technique. The research instruments included initial ability tests, creativity tests based on open-ended math problems, and interviews. The results of descriptive statistical analysis show that most students in class X Merdeka 8 SMA Negeri 1 Polewali have initial abilities that are classified as moderate, with a percentage reaching 50%. Meanwhile, the level of student creativity is in the moderately creative category with a percentage of 55.3%. The results of inferential analysis show that there is a significant positive influence between initial ability and creativity of students in class X Merdeka 8 SMA Negeri 1 Polewali. This is indicated by the relationship between the two variables with a p-value of 0.024 (p < 0.05). This finding indicates that the higher the students' initial ability, the greater the influence in improving their creativity in solving math problems. Keywords: Initial Ability, Creativity, Open-Ended Mathematics Problems, Students, High School.